2014
DOI: 10.1002/14651858.cd006640.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid for upper gastrointestinal bleeding

Abstract: Background Tranexamic acid reduces haemorrhage through its antifibrinolytic effects. In a previous version of the present review, we found that tranexamic acid may reduce mortality. This review includes updated searches and new trials.Objectives To assess the effects of tranexamic acid versus no intervention, placebo or other antiulcer drugs for upper gastrointestinal bleeding.Search methods We updated the review by performing electronic database searches (Cochrane Central Register of Controlled Trials (CENTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 45 publications
5
98
0
6
Order By: Relevance
“…There is some evidence for its benefit in acute GI bleeding. Several trials of tranexamic acid in UGIB have been carried out,125 which on pooled analysis showed a 40% risk reduction in mortality 126. However, this treatment benefit for mortality was no longer apparent when the analysis was limited to trials at low risk of bias.…”
Section: Drug Therapy Considerations In Acute Lgibmentioning
confidence: 99%
“…There is some evidence for its benefit in acute GI bleeding. Several trials of tranexamic acid in UGIB have been carried out,125 which on pooled analysis showed a 40% risk reduction in mortality 126. However, this treatment benefit for mortality was no longer apparent when the analysis was limited to trials at low risk of bias.…”
Section: Drug Therapy Considerations In Acute Lgibmentioning
confidence: 99%
“…A Cochrane review has found benefit in use of tranexamic acid (TXA) in upper gastrointestinal bleeding. 50 Similarly, a meta-analysis of randomized controlled trials found the use of TXA in liver transplantation to be safe and effective. 51 With little risk and the potential for benefit, the use of TXA in patients with liver disease and clinically significant bleeding, antifibrinolytics should be considered.…”
Section: Antithrombotic Prophylaxismentioning
confidence: 99%
“…Tranexamic acid is able to bind with receptors on both plasminogen and plasmin and it can act as an antifibrinolytic factor. As suggested by other studies, tranexamic acid is potentially effective for managing gastrointestinal hemorrhage [9].…”
Section: Introductionmentioning
confidence: 69%